Generalized Truncated Methods for an Efficient Solution of Retrial Systems. (2008) - Domenech-Benlloch, Ma Jose; Gimenez-Guzman, Jose Manuel; Pla, Vicent; Martinez-Bauset, Jorge; Casares-Giner, Vicente
Abstract : We are concerned with the analytic solution of multiserver retrial queues including the impatience phenomenon. As there are not closed-form solutions to these systems, approximate methods are required. We propose two different generalized truncated methods to effectively solve this type of systems. The methods proposed are based on the homogenization of the state space beyond a given number of users in the retrial orbit. We compare the proposed methods with the most well-known methods appeared in the literature in a wide range of scenarios. We conclude that the proposed methods generally outperform previous proposals in terms of accuracy for the most common performance parameters used in retrial systems with a moderated growth in the computational cost.